Perfect phrases for communicating change : hundreds of ready-to-use phrases for maintaining focus and productivity during organizational change - Polsky, Lawrence; Gerschel, Antoine (New York : McGraw-Hill, 2010)
"Employees respond to organizational change with worry, fear, and sometimes even panic. Your job is to keep them motivated and focused - so you must choose your words carefully during times of upheaval. Perfect Phrases for Communicating Change has hundreds of ready-to-use phrases for ensuring your employees make the transition with clarity, commitment, and skill. Learn the most effective language for: Articulating new company initiatives ; Responding to questions with confidence ; Easing employees' fears ; Clarifying roles and responsibilities ; Addressing resistance and performance problems." -- Cover
1. Laying the foundation for communicating change -- 2. Perfect phrases for communicating a new organizational structure -- 3. Perfect phrases for communicating a new project -- 4. Perfect phrases for communicating as a new leader -- 5. Perfect phrases for communicating a new organizational strategy -- 6. Perfect phrases for handling resistance
Includes bibliographical references and index
Keywords: Communication in management; Communication in organizations; Organizational change